Tutors’ experiences of implementing a bilingual language policy at the University of KwaZulu-Natal - Nsele, Sanele; Mthembu, Bheki; Mhlongo, Bonakele (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The University of KwaZulu-Natal (UKZN) identifies with the goals of South Africa’s Higher Education Institutions multilingual language policy and seeks to be a key player in the implementation thereof. The multilingual policy recognizes the need to develop and promote the use of indigenous languages as languages of teaching and learning alongside English and Afrikaans. In pursuit of this policy, the University has embarked on a number of programmes, one of which is the Bilingual Tutoring Programme which promotes the use of English and isiZulu as languages of teaching and learning. This paper explores implementation challenges and opportunities experienced by tutors within selected academic programmes. Data were generated through questionnaires, semi-structured interviews and focus group discussions. The study including its inductive thematic analysis was undergirded by Vygotsky’s (1978) construct of the Zone of Proximal Development. The study’s findings were both positive and negative. According to participants, findings indicate that tutors and lecturers lack understanding of the UKZN Language Policy as a result of what appears to be the University’s lack of will to champion its policy. However, the findings also revealed that the use of bilingualism revitalizes student centered learning and animated interactions and raises interest among students. Among the recommendations, is the importance of encouraging the co-operation of all university stakeholders so as to promote success and engender an ultimate sense of ownership
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Bilingual tutorials; Bilingual Language policy; Zone of Proximal Development; Tutors and tutoring; Language policy -- South Africa; Education, Bilingual; Language and languages -- Study and teaching -- Bilingual method